Co-creating a learning community on sustainability: Teaching sustainability in Higher Education - Andersson, Gunnar (International Transitions, 2024)
This study explores the emergence of a distinctive learning community part of teaching sustainability. It uses action nets to describe major contributions shaping a learning community on sustainability. The results describe how the growing learning community of research, externally funded projects, teaching, students, NGOs, and regional industry is framed within a sociotechnical network of actants and identifies disruptions and events exposing the transitions in the making. Based on the findings we discuss lessons learned from the co-creation increasing the awareness of mechanisms involved in gaining (and regaining) needed to create the new approach to teaching sustainability. The learning community mirrors in many ways the systemic nature of sustainability and sustainable development. It also introduces the uncertainty and ambiguity inherent in the transition. It was easier than anticipated to mobilize resources, but the bounds connecting the different contributions are also delicate and we experience the learning community as a fresh produce, something we must create and recreate continuously.